Pengaruh faktor eksternal terhadap disposisi produktif pada kecakapan matematis - Hidayat, Azhar Majid; Dasari, Dadan; Priatna, Bambang Avip (IKIP Siliwangi, 2024)
This research aims to determine the extent to which family factors and school factors influence productive dispositions. The research method used in this research is explanatory research with a quantitative approach and data processing from non-test data using confirmatory factor analysis and Structural Equation Modeling (SEM). Research data was obtained by distributing a 37 item questionnaire to 103 subjects. From the research results processed using AMOS software, family factors do not significantly influence productive disposition. Meanwhile, school factors influence productive dispositions significantly and provide the most dominant overall influence compared to family.